1944
DOI: 10.1002/hlca.194402701124
|View full text |Cite
|
Sign up to set email alerts
|

Strukturchemische Untersuchungen XIII. Zur Kenntnis des Malonsäure‐dithio‐amids

Abstract: Die Analyse stimmb auf das zu erwartende 1,4-Di-[4-methyl-thiazolyl-(2)]-benzol (I) : -1,347 mg Subst. gaben 0,118 cm3 ?Sa (17O, 744 mm) C,,H12N2S, Ber. N 10,2S Gef. N 10,100/, 2,715 mg Subst. gaben 0,365 cm3 N, (ISo, 742 mm) C,,Hl,0,,N8S, Ber. N 15,34 Gef. N 15,400G Pikrat: Gelbe Krystalle (aus Alkohol), Smp. 212O K o n d e n s a t i o n m i t w -B r o m a c e t o p h e n o n . 0,2 g Dithio-terephthalshre-diamid wurden in 40 cm3 Xitrobenzol in der Hitze gelost und mit 0,45 g w-Bromacetophenon versetzt. Die Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1959
1959
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The resulting mixture was neutralized with aqueous NaHCO 3 , and extracted with CHCl 3 . The solvent was removed from the dried combined organic layers to leave a brown solid which was submitted to flash chromatography (CH 2 Cl 2 - AcOEt, 4:1) on silica gel and then crystallized to a white solid (1.04 g, 3.11 mmol, 78%): mp 110−111 °C (toluene) (lit . mp 119−120 °C); 1 H NMR (CDCl 3 ) δ 7.91 (d, 4H, J = 8.1), 7.47−7.31 (m, 8H), 4.84 (s, 2H).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting mixture was neutralized with aqueous NaHCO 3 , and extracted with CHCl 3 . The solvent was removed from the dried combined organic layers to leave a brown solid which was submitted to flash chromatography (CH 2 Cl 2 - AcOEt, 4:1) on silica gel and then crystallized to a white solid (1.04 g, 3.11 mmol, 78%): mp 110−111 °C (toluene) (lit . mp 119−120 °C); 1 H NMR (CDCl 3 ) δ 7.91 (d, 4H, J = 8.1), 7.47−7.31 (m, 8H), 4.84 (s, 2H).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to o-phthalonitrile, malononitrile was found to form dithionmalonamide on reaction with hydrogen sulfide in cold alcoholic solution containing potassium ethoxide (199). In similar fashion, adiponitrile gave dithionadipamide (92).…”
Section: Thionamides From Nitriles and Cyanogenmentioning
confidence: 95%
“…This dione gave high-melting polymers on condensation with either dithionoxamide (172) or dithionterephthalamide, l,4-(H2NCS)2CaH4 (93). With dithionmalonamide, a highly colored product was obtained (199). It was suggested that this color might be due to chromophores in a structure such as the following: V-V Thionformamide behaves somewhat differently toward -halo carboxylic acids than do its higher homologs (248).…”
Section: Miscellaneous Reductionsmentioning
confidence: 99%
“…To a dispersion of 2.8 g (10 mmol) of compound I in 20 ml of pyridine was added 1.4 ml (10 mmol) of triethylamine, and a moderate fl ow of hydrogen sulfi de was bubbled for 2 h. Afterwards the mixture was maintained in a refrigerator for 24 h. The formed precipitate was fi ltered off, washed with ethanol and hexane. Yield 0.3 g (46%), yellow powder, mp 188-190°S (212°C [4]). 1 H NMR spectrum, δ, ppm: 3.79 s (2H, CN 2 ), 9.32 br.s (2H, NH 2 ), 9.62 br.s (2H, NH 2 ).…”
Section: -Amino-188-trimethyl-3-dicyanomethylene-2-azabicyclo[22mentioning
confidence: 99%